Glycines from the APP GXXXG/GXXXA Transmembrane Motifs Promote Formation of Pathogenic Aβ Oligomers in Cells - Decock, Marie; Stanga, Serena; Octave, Jean-Noël; Dewachter, Ilse; Smith, Steven O.; Constantinescu, Stefan N.; Kienlen-Campard, Pascal (Frontiers in Aging Neuroscience, 2016)
Alzheimer’s disease (AD) is the most common neurodegenerative disorder characterized by progressive cognitive decline leading to dementia. The amyloid precursor protein (APP) is a ubiquitous type I transmembrane (TM) protein sequentially processed to generate the β-amyloid peptide (Aβ), the major constituent of senile plaques that are typical AD lesions. There is a growing body of evidence that soluble Aβ oligomers correlate with clinical symptoms associated with the disease. The Aβ sequence begins in the extracellular juxtamembrane region of APP and includes roughly half of the TM domain. This region contains GXXXG and GXXXA motifs, which are critical for both TM protein interactions and fibrillogenic properties of peptides derived from TM α-helices. Glycine-to-leucine mutations of these motifs were previously shown to affect APP processing and Aβ production in cells. However, the detailed contribution of these motifs to APP dimerization, their relation to processing, and the conformational changes they can induce within Aβ species remains undefined. Here, we describe highly resistant Aβ42 oligomers that are produced in cellular membrane compartments. They are formed in cells by processing of the APP amyloidogenic C-terminal fragment (C99), or by direct expression of a peptide corresponding to Aβ42, but not to Aβ40. By a point-mutation approach, we demonstrate that glycine-to-leucine mutations in the G29XXXG33 and G38XXXA42 motifs dramatically affect the Aβ oligomerization process. G33 and G38 in these motifs are specifically involved in Aβ oligomerization; the G33L mutation strongly promotes oligomerization, while G38L blocks it with a dominant effect on G33 residue modification. Finally, we report that the secreted Aβ42 oligomers display pathological properties consistent with their suggested role in AD, but do not induce toxicity in survival assays with neuronal cells. Exposure of neurons to these Aβ42 oligomers dramatically affects neuronal differentiation and, consequently, neuronal network maturation.